O ensino de geografia e a condição docente: subsídios à educação ambiental - Andrade, Jeferson Monteiro de (2017)
In the last decades, society's concern with environmental issues has grown. These concerns, however, generate conflicts of interest in different human groups. In education this materializes in proposals with environmental adjectives and must be present in all education levels. It will also be conflicting. Each proposal of Environmental Education is a reflection of the worldview about conflicting human groups. There are several pedagogical tendencies in environmental education. Specialists point out three main pedagogical macrotrends: one classified as conservationist because it is based on conservation and coexistence with nature, another pragmatic based on the search for environmental solutions by the market and a critique that seeks the transformation of the society paradigms. The Environmental Education to become effective in basic education needs the contribution of the different areas of knowledge, among them Geography, one of the sciences that historically deals with what is now called the environment. Thus, we seek to know more about the following question: what obstacles and possibilities exist in an attempt to build an environmental education, critical from the teaching of Geography, at a school in the public system of basic education in Minas Gerais? The main objective was to carry out an environmental education experience, critical, based on the teaching of Geography, at a school in the public system of basic education in Minas Gerais. From that, knowing the obstacles and possibilities of this experience, including looking at the possibilities of realizing in the future an experience on similar bases that is interdisciplinary. To achieve these objectives, a case study was carried out on the teaching practice of the author of this research, where the theme was related to the content defined in the lesson plan and defined with the students. At the end of the research it was noticed that the culture of authoritarianism negatively influences the condition of teaching work. It was observed that, with greater freedom and autonomy, students seen as problematic will have better results. It was also realized that it is important to cultivate the habit of having records about the practice of class. They were as basis for the exchange of strategies and impressions among teachers. In addition, the lack of permeability of Environmental Education of critical macro-trends in basic education makes it difficult to construct interdisciplinary practices, especially those related to environmental issues.